Leverage points to pathways for the transformation of agri-food systems - Nicholas R Magliocca; Emily K Burchfield; Emma Chapman Busby; Eve Brantley; Olivia Cleveland; Walter L Ellenburg; Kaitlin Fischer; Mukesh Kumar; Vikalp Mishra; Darrell McGuire; Udaysankar S Nair; Arlo Pate; et al. (Environmental Research: Food Systems, 2025)
Achieving large-scale, transformative climate change adaptations in agriculture while mitigating further climate impacts and supporting sustainable and equitable rural livelihoods is a grand challenge for society. Transformation of the agri-food system is necessary and inevitable, but the extent to which transformation can be intentionally guided toward desirable states remains unclear. We argue that, instead of targeting leverage points (LPs) in isolation, coordinated interventions at multiple LPs and their interactions are necessary to create a broader system transformation toward more adaptive futures. Using the southeastern United States of America as a case study, we conceptualize a way of doing transformation research in agri-food systems that integrates multiple theoretical and practical perspectives of how transformative pathways can be constructed from ‘chains’ of interacting LPs. We outline several principles for transformative research, the core of which are participatory, transdisciplinary, and convergence research methods needed for articulating a shared vision. These principles embrace an action-oriented approach to research in which the act of assembling diverse networks of researchers, stakeholders, and community partners itself can activate community- and regional-level LPs to scale up changes. Finally, we present tangible examples of specific LPs and their interactions targeted by agri-food system interventions currently underway or planned. This work offers an ‘anticipatory’ vision for agri-food system transformation research that recognizes the need to normatively create an enabling environment to build momentum toward shared visions of secure, equitable, and sustainable regional agri-food systems.